ANTIMICROBIAL RESISTANCE PATTERNS AND SUSCEPTIBILITY PROFILES OF UROPATHOGENS AT TRA VINH GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Urinary tract infections (UTIs) are among the top five most common hospital-acquired infections. Annually, millions of patients are affected by healthcare-associated UTIs, posing a major challenge to medical facilities worldwide.Objective: To determine the antimicrobial resistance patterns and susceptibility profiles of each uropathogen isolated from inpatients with suspected UTIs who underwent urine culture at Tra Vinh General Hospital.Materials and Methods: A descriptive, retrospective cross-sectional study was conducted on 132 patients (or episodes). Bacterial strains were identified and antimicrobial susceptibility testing (AST) was performed using the Vitek 2 automated system. Data were recorded from medical records.Results: E. coli exhibited high resistance rates of >80% to Ampicillin, Piperacillin, and Fluoroquinolones (Ciprofloxacin). Bacterial isolates were more frequent than fungi (23.48% vs 8.33%). K. pneumoniae demonstrated 100% resistance to Ampicillin, Ampicillin-sulbactam, Cefepime, and Cefoxitin; resistance to Carbapenems, Aminoglycosides, and Fluoroquinolones ranged from 80% to 100%; and resistance to Cephalosporins exceeded 66.67%. P. aeruginosa showed a 50% resistance rate to Piperacillin-tazobactam, Piperacillin, Ceftazidime, Imipenem, Meropenem, and Ciprofloxacin. P. mirabilis was 100% resistant to Ampicillin, Piperacillin, Ciprofloxacin, and Tigecycline.Conclusion: It is essential to prioritize urine culture and antimicrobial susceptibility testing before antibiotic administration to guide appropriate treatment regimens, prevent misuse, and mitigate the risk of escalating antimicrobial resistance.
Keywords: Urinary tract infection, E. coli, K. pneumoniae, P. aeruginosa, Tra Vinh.